Private Equity and Financial Development in Latin America - Puente, Ignacio (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Shallow capital markets are a key bottleneck for private sector development in Latin America. Still, there is not a large literature on capital markets and corporate governance, or on the politics of regulatory reform and business associations, focused on this region. To help address this gap, this new book introduces private equity into the financial development debate through a Latin American lens. The author looks at the cases of Brazil, Mexico, Chile, Colombia, and Argentina. And proposes a shift in the financial development discussion from institutional explanations focused only on rules to an actor-based argument centered on the role of institutional investors, in particular pension funds . Ignacio Puente is a researcher working on the political economy of financial development and corporate governance reform in emerging economies. .
Chapter 1. Introduction -- Chapter 2. Private Equity, Financial Development and Corporate Governance Reform -- Chapter 3. Private Equity and Latin America -- Chapter 4. Institutions: From Rules to Investors -- Chapter 5. Business Association and the Politics of Regulatory Reform -- Chapter 6. Beyond Latin America -- Chapter 7. Conclusions: Private Equity and Development.
Keywords: Economic development; America-Politics and government; Economics; Comparative government; Development Studies; American Politics; Political Economy and Economic Systems; Comparative Politics